2011
DOI: 10.1001/jama.2011.520
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin E or Metformin for Treatment of Nonalcoholic Fatty Liver Disease in Children and Adolescents

Abstract: Context Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease in US children and adolescents and can present with advanced fibrosis or non-alcoholic steatohepatitis (NASH). No treatment has been established. Objective To determine whether children with NAFLD would improve from therapeutic intervention with vitamin E or metformin. Design, Setting, and Patients Randomized, double-blind, double-dummy, placebo-controlled clinical trial conducted at 10 university clinical research ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
741
2
23

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 974 publications
(825 citation statements)
references
References 19 publications
13
741
2
23
Order By: Relevance
“…Although metformin is suggested as a first‐line pharmacologic treatment for prediabetes and T2D, several randomized controlled trials (RCTs) reported no effects of metformin on histologic improvement of NAFLD in either children or adults 14, 15. However, metformin may help with weight loss and may lower the risk of HCC in patients with diabetes 16.…”
Section: Nafld/nash‐specific Therapiesmentioning
confidence: 99%
“…Although metformin is suggested as a first‐line pharmacologic treatment for prediabetes and T2D, several randomized controlled trials (RCTs) reported no effects of metformin on histologic improvement of NAFLD in either children or adults 14, 15. However, metformin may help with weight loss and may lower the risk of HCC in patients with diabetes 16.…”
Section: Nafld/nash‐specific Therapiesmentioning
confidence: 99%
“…The primary outcomes was a sustained reduction in alanine transferase whilst secondary outcomes were improvement in histological features and resolution of nonalcoholic steatohepatitis (NASH). Although the primary outcome was not achieved, vitamin E was associated with resolution of NASH and an improvement in hepatocyte ballooning suggesting the need for future studies [129].…”
Section: Key Management Issuesmentioning
confidence: 95%
“…The study also reported an improvement in liver enzymes, insulin resistance and serum lipid levels [128]. The TONIC study, a double-blind placebo controlled trial compared vitamin E or metformin for 96 weeks [129]. The primary outcomes was a sustained reduction in alanine transferase whilst secondary outcomes were improvement in histological features and resolution of nonalcoholic steatohepatitis (NASH).…”
Section: Key Management Issuesmentioning
confidence: 99%
“…Considering that insulin resistance is the hallmark of NAFLD, drugs acting on glucose metabolism have long been considered for NAFLD treatment [35,58,[72][73][74][75][76][77][78][79][80]. Insulin sensitizers have been tested in several clinical trials of different duration.…”
Section: Drug Treatment Of Nafld With a Defined Impact On Glucose Metmentioning
confidence: 99%
“…This therapeutic effect has been demonstrated with metformin, which is the basis of diabetes treatment and significantly reduces the progression of pre-diabetes to diabetes in several large intervention trials. However, initial evidence for an effect of metformin on NAFLD histology was not confirmed [72,76,77,80], and the effects of metformin on liver disease progression have been questioned [81]. Many more data are available with the peroxisome-proliferator activator receptor- (PPAR-) agonists (glitazones) as insulin sensitizers.…”
Section: Drug Treatment Of Nafld With a Defined Impact On Glucose Metmentioning
confidence: 99%